International teleconsultation on conjoined twins leading to a successful separation: a case report. (August 2018) - Fusaro, Mario V; Becker, Christian; Pandya, Samir; Mcbride, Whitney; Alizadeh, Kaveh; Iannotti, Vicki; Zelkovic, Paul; Barst, Samuel; Tobias, Michael E; Mohan, Avinash; Freda, Jeffrey; Gewitz, Michael; et al.
Conjoined twins are identical twins that have incompletely separated in utero . The prognosis for conjoined twins is poor and management in a skilled tertiary care centre is paramount for definitive care. We describe our experience with a telemedical consultation on conjoined twins in The Dominican Republic from our eHealth centre in Valhalla, NY. The patients were two month old, female, pygopagus conjoined twins. A multidisciplinary teleconference was initiated with the patients, their family, the referring paediatrician and our team. Based on this teleconsultation, the team felt as though the twins may be amenable to a surgical separation. They presented to our centre in Valhalla, NY, for a detailed physical examination and series of imaging studies. Soon after, the patients underwent a successful 21 h separation procedure and were discharged 12 weeks later. To our knowledge, this is one of the first reports of an international teleconsultation leading to a successful conjoined twin separation procedure.